CFD Study of Tidal Current Turbine Shroud for Initial Design Evaluation - Azim, Arshad; Shahrani, Anuar; Ahmmad Shukrie, Md Yudin; Rosdi, Hussin (2014)
CFD simulation of a tidal current turbine shroud was performed using Ansys FLUENT commercial code and comparison was made with experimental data. The simulation result obtained was in good agreement with the experimental data. The coefficient of velocity, Cv was in the range of approximately 1.2 to 1.4 for both simulation and experiment. The present study gave useful information on the viability of CFD simulation for the initial evaluation of shroud design performance.